2016
DOI: 10.1002/cncy.21762
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transcription–polymerase chain reaction molecular testing of cytology specimens: Pre‐analytic and analytic factors

Abstract: The introduction of molecular testing into cytopathology laboratory practice has expanded the types of samples considered feasible for identifying genetic alterations that play an essential role in cancer diagnosis and treatment. Reverse transcription–polymerase chain reaction (RT‐PCR), a sensitive and specific technical approach for amplifying a defined segment of RNA after it has been reverse‐transcribed into its DNA complement, is commonly used in clinical practice for the identification of recurrent or tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 65 publications
1
32
0
2
Order By: Relevance
“…Even with optimised digestion and heating steps, however, it is not possible to completely remove all chemical modifications such as residual methyl groups from FFPE-extracted RNA. 14 Cellularity is evaluated by examining an H&E-stained section prepared from the CB; thus, the percentage of tumour cells in deeper sections of the CB used for molecular testing is assessed in an extrapolative fashion inferred but not actually known. When the tumour cellularity is high and more than sufficient for testing, paraffin scrolls can simply be placed directly into a tube for extraction without microdissection, and cellularity assessment of an H&E section taken after the scrolls (postcurl section) may be unnecessary.…”
Section: Cell Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with optimised digestion and heating steps, however, it is not possible to completely remove all chemical modifications such as residual methyl groups from FFPE-extracted RNA. 14 Cellularity is evaluated by examining an H&E-stained section prepared from the CB; thus, the percentage of tumour cells in deeper sections of the CB used for molecular testing is assessed in an extrapolative fashion inferred but not actually known. When the tumour cellularity is high and more than sufficient for testing, paraffin scrolls can simply be placed directly into a tube for extraction without microdissection, and cellularity assessment of an H&E section taken after the scrolls (postcurl section) may be unnecessary.…”
Section: Cell Blockmentioning
confidence: 99%
“…2 The advantage of a short acquisition time for molecular processing is mostly required to ensure high-integrity RNA for some molecular applications such as complementary DNA labelling for microarray analysis and transcriptome analysis. 14 In contrast, RT-PCR or quantitative RT-PCR analysis for fusion gene detection is more tolerant of partially degraded RNA because the design can be based on an analysis of smaller regions of RNA. 14 For long-term storage, aliquots can be frozen at 80°C RNA later or similar RNA stabilising solutions and stored in freezers 34 ; fresh cells can also be stored at room temperature for months in Whatman filter paper cards (GE Healthcare Life Sciences, Buckinghamshire, England).…”
Section: Fresh Cellsmentioning
confidence: 99%
“…Non-cross-linking alcoholic reagents may yield superior results as RNA fixatives in comparison with aldehydes because they cause little chemical change and usually provide higher quality nucleic acids for molecular testing than do FFPE sections 14. Several studies using previously stained cytology smears have shown that molecular testing can be performed successfully using both Diff-Quik as well as Papanicolaou-stained slides.…”
Section: Direct Smearsmentioning
confidence: 99%
“…In addition, residual material from CytoLyt samples has been shown to feature optimal RNA integrity being suitable for nucleic acid isolation and subsequent analysis by reverse transcription-PCR (RT-PCR) 31. However, RNA degradation was reported in specimens stored for 12 months at room temperature, and long-term storage requires –80°C 14. Interestingly, also, exfoliative oral cytology specimen has shown an adequate RNA preservation 31…”
Section: Liquid-based Cytologymentioning
confidence: 99%
See 1 more Smart Citation